2014
DOI: 10.2967/jnmt.113.134940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Objective Striatal Analysis Program for Determining Laterality in Uptake of 123I-Ioflupane SPECT Images: Comparison to Clinical Symptoms and to Visual Reads

Abstract: The OSA program may be a helpful aid in the interpretation of (123)I-ioflupane SPECT images for determining laterality representing the asymmetric loss of dopamine transporters in the striata. OSA offers an objective, reproducible over-read evaluation for the laterality of onset in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However, it should be noted that normal distribution and the hereby described abnormal patterns in different parkinsonian syndromes are expected to be very similar for DAT SPECT and [ 18 Some of them include a one-or two-step-based fully automated registration of the patient SPECT scan to a template or to an averaged, spatially normalized brain volume. Predefined VOIs are then automatically placed on the striatal and the background regions [82][83][84][85][86][87][88].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that normal distribution and the hereby described abnormal patterns in different parkinsonian syndromes are expected to be very similar for DAT SPECT and [ 18 Some of them include a one-or two-step-based fully automated registration of the patient SPECT scan to a template or to an averaged, spatially normalized brain volume. Predefined VOIs are then automatically placed on the striatal and the background regions [82][83][84][85][86][87][88].…”
mentioning
confidence: 99%
“…Some studies have reported a mild reduction of PCR with age, but there are conflicting data in the literature on this topic (possibly due to the number and age range of included subjects and the modalities of VOI drawing) [87]. Evaluation of asymmetry between left and right sides is also useful in the earliest stages, although mild asymmetry between striata or striatal subregions may occur in normal subjects [88].…”
mentioning
confidence: 99%
“…6 In order to aid the clinician with assessing the quantitative loss of DaT sites in patients, several image processing methods have been developed. [7][8][9][10][11][12][13][14][15][16][17] Computer-aided analysis can provide critical adjunct information, a "second read," which may be particularly useful for challenging cases 18,19 ; however, a criterion standard for testing the validity of automated methods is desirable.…”
mentioning
confidence: 99%
“…In recent years, our group has developed an automated software program for semiquantitative analysis of striatal 123 I-ioflupane uptake. We have demonstrated good correlation between expert reads and semiquantitative analysis of the images, 18,19 yet the analysis needs to be optimized and validated. The Parkinson's Progression Markers Initiative (PPMI) offers an unprecedented opportunity for testing the validity of an automated analysis software for quantitating 123 I-ioflupane DaT SPECT scans (from here on "DaT scans").…”
mentioning
confidence: 99%
“…To aid the clinician with assessing the quantitative loss of dopaminergic transporter sites in patients, several image processing software packages have been developed over the years (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Computer-aided analysis can provide critical adjunct information or a ''second read,'' which may be particularly useful for challenging cases (15)(16)(17).…”
mentioning
confidence: 99%